Retentive strength of different intracanal posts in restorations of anterior primary teeth: an in vitro study - Mahtab Memarpour; Fereshteh Shafiei; Maryam Abbaszadeh (Korean Academy of Conservative Dentistry, 2013)
Objectives To determine the retentive strength and failure mode of undercut composite post, glass fiber post and polyethylene fiber post luted with flowable composite resin and resin-cement. Materials and Methods Coronal parts of 120 primary canine teeth were sectioned and specimens were treated endodontically. The teeth were randomly divided into 6 groups (n = 20). Prepared root canals received intracanal retainers with a short composite post, undercut composite post, glass fiber post luted with flowable resin or resin-cement, and polyethylene fiber post luted with flowable resin or resin-cement. After crown reconstruction, samples were tested for retentive strength and failure mode. Statistical analysis was done with one-way ANOVA and Tukey tests (p < 0.05). Results There were statistically significant differences between groups (p = 0.001). Mean bond strength in the undercut group was significantly greater than in the short composite post (p = 0.030), and the glass fiber post (p = 0.001) and the polyethylene fiber post group luted with resin-cement (p = 0.008). However, the differences between the undercut group and the groups with flowable composite as the luting agent were not significant (p = 0.068, p = 0.557). Adhesive failure was more frequent in the fiber post groups. Conclusions Although the composite post with undercutting showed the greatest resistance to dislodgement, fiber posts cemented with flowable composite resin provided acceptable results in terms of retentive strength and fracture mode.